Probing the rate-determining region of the potential energy surface for a prototypical ion–molecule reaction. (13th March 2018) - Xie, Changjian; Liu, Xinguo; Sweeny, Brendan C.; Miller, Thomas M.; Ard, Shaun G.; Shuman, Nicholas S.; Viggiano, Albert A.; Guo, Hua
Abstract : We report a joint experimental–theoretical study of the F – + HCl → HF + Cl − reaction kinetics. The experimental measurement of the rate coefficient at several temperatures was made using the selected ion flow tube method. Theoretical rate coefficients are calculated using the quasi-classical trajectory method on a newly developed global potential energy surface, obtained by fitting a large number of high-level ab initio points with augmentation of long-range electrostatic terms. In addition to good agreement between experiment and theory, analyses suggest that the ion–molecule reaction rate is significantly affected by shorter-range interactions, in addition to the traditionally recognized ion–dipole and ion–induced dipole terms. Furthermore, the statistical nature of the reaction is assessed by comparing the measured and calculated HF product vibrational state distributions to that predicted by the phase space theory. This article is part of the theme issue 'Modern theoretical chemistry'.